Freezing of water droplets on solid surfaces: An experimental and numerical study - Chaudhary, Gaurav; Li, Ri (Experimental thermal and fluid science, 2014)
•We study the heat transfer of water droplets freezing on supercooled surfaces.•A droplet changing from water to ice shows four distinct consecutive processes.•Nucleation during recalescence results in ultrafast rise of droplet temperature.•A long freezing process follows recalescence and is driven by heat transfer.•Pre-recalescence temperature and surface wettability affect droplet freezing time. We present an experimental and numerical study on the freezing of static water droplets on surfaces with different wettability when the surfaces are subject to rapid cooling. Temperature evolution of the droplets is recorded using both intrusive and non-intrusive methods to identify the processes involved in the cooling and phase change of the droplets. It is found the time taken for a droplet to freeze depends on the droplet temperature at the pre-recalescence instant as well as the surface wettability. To provide insight into the heat transfer during the freezing process, thermal simulation is carried out by numerically solving the enthalpy-based heat conduction equation. To determine the initial and boundary conditions for the simulation of freezing, the thermal history of the droplet prior to the occurrence of freezing is numerically analyzed by solving single phase heat conduction driven by rapid cooling. The numerical results of droplet freezing are compared to the experimental data, showing close agreement on the freezing time.